Ruthenium Oxide/Reduced Graphene Oxide Nanoribbon Composite and Its Excellent Rate Capability in Supercapacitor Application. Issue 1 (15th December 2015) - Wang, Ruijing; Jia, Pengfei; Yang, Yuying; An, Ning; Zhang, Yadi; Wu, Hongying; Hu, Zhongai
Abstract: Chemical oxidation is used to cut and unzip multi‐walled carbon nanotubes in the transverse direction and the axial direction to form graphene oxide nanoribbon (GONR). Ruthenium oxide/reduced graphene oxide nanoribbon composite (RuO2 /rGONR) with a 72.5 wt% RuO2 loading is synthesized through an aqueous‐phase reaction, in which GONR is served as starting material, followed by mild thermal treatment in ambient air. The resulting RuO2 /rGONR composite achieves specific capacitance up to 677 F·g −1 at the current density of 1 A·g −1 in three‐electrode system using 1 mol·L −1 H2 SO4 as electrolyte. The resultant electrode exhibits an excellent rate capability (91.8% retention rate at 20 A·g −1 ). Especially, the symmetric supercapacitor assembled on the basis of RuO2 /rGONR electrode delivers high energy density (16.2 Wh·kg −1 ) even at the power density of 9885 W·kg −1, which is very essential for supercapacitors. Abstract : rGONR was uniformly coated by RuO2 particles using a facile route. With unique microstructure and high RuO2 loading, the electrode material exhibits a high specific capacitance, and excellent rate capability.